2019
DOI: 10.1016/j.compositesb.2019.02.033
|View full text |Cite
|
Sign up to set email alerts
|

Vibration and buckling behaviours of thin-walled composite and functionally graded sandwich I-beams

Abstract: The paper proposes a Ritz-type solution for free vibration and buckling analysis thinwalled composite and functionally graded sandwich I-beams. The variation of material through the thickness of functionally graded beams follows the power-law distribution.The displacement field is based on the first-order shear deformation theory, which can reduce to non-shear deformable one. The governing equations of motion are derived from Lagrange's equations. Ritz method is used to obtain the natural frequencies and criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 50 publications
1
9
0
4
Order By: Relevance
“…For open-section profiles, angle-ply laminates obtained a higher buckling load than quasi-isotropic laminates [ 113 ]. The buckling capacity of these profiles was decreasing when the fibre angle was increased and the cross-ply laminates were observed to sustain a larger buckling load than angle-ply when the fibre angle is larger than [ 58 , 80 ]. It was found that the effect of the stacking sequence on the buckling capacity of laminated plates decreases as their dimensions are increased [ 128 ] but it becomes significant in open-section structural-level columns with slender walls [ 140 ].…”
Section: Layup Parameters Of Hollow Box Pfrp Profilesmentioning
confidence: 99%
“…For open-section profiles, angle-ply laminates obtained a higher buckling load than quasi-isotropic laminates [ 113 ]. The buckling capacity of these profiles was decreasing when the fibre angle was increased and the cross-ply laminates were observed to sustain a larger buckling load than angle-ply when the fibre angle is larger than [ 58 , 80 ]. It was found that the effect of the stacking sequence on the buckling capacity of laminated plates decreases as their dimensions are increased [ 128 ] but it becomes significant in open-section structural-level columns with slender walls [ 140 ].…”
Section: Layup Parameters Of Hollow Box Pfrp Profilesmentioning
confidence: 99%
“…where U j , V j , W j and φ j are unknown and need to be determined; ϕ j (x) are approximation functions [21]. It should be noted that these approximation functions in Table 1…”
Section: Ritz Solutionmentioning
confidence: 99%
“…Vo and Lee [16,17] used FEM for flexural-torsional stability analysis of thin-walled composite beams. In recent years, buckling behaviours of thin-walled functionally grade open section beams are also analysed [18][19][20][21]. It can be seen that Ritz method has seldom been used to analyse the buckling problem of thin-walled composite channel beams.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the critical buckling load decreased by 35% when the fibre angle increased from 10° to 30° for the unidirectional composite profile [20]. The cross-ply laminate was observed to sustain a larger buckling load than angle-ply laminate when the fibre angle is larger than 30 [21,22]. In general, balanced and symmetric laminate is preferred to minimise the manufacturing imperfection and limit the elastic coupling effect and warp [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The buckling load capacity of filament-wound Glass Fibre-Reinforced Polymer (GFRP) profiles subjected to compression was increased by 20% when the winding angle was increased from 30 to 60 [19]. The effect of the fibres orientation on the buckling load of FRP composite profiles made with unidirectional [20], angle-ply, and cross-ply [21,22] layups and subjected to axial compression was studied numerically. It was found that the critical buckling load decreased by 35% when the fibre angle increased from 10° to 30° for the unidirectional composite profile [20].…”
Section: Introductionmentioning
confidence: 99%